20th Anniversary Editorial - Maja Klun; Stanka Setnikar Cankar; Polonca Kovač (Central European Public Administration Review)
In honor of CEPAR's 20th anniversary, we have invited present and past editors to offer some thoughts on the journal's founding and its evolution over two decades of publishing.